ON UZBEKISTAN’S GRAND STRATEGY - TOLIPOV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2011)
Ater ten years of independence, the Republic of Uzbekistan has become a strategic partner of the United States, an unprecedented geopolitical event: for the first time in its history, Central Asia, which for centuries remained on the sidelines of world politics, has found itself in the limelight of the global and regional powers.After twenty years of independent development, the Central Asian countries are still coping with the fundamental task of formulating adequate foreign policy strategies.This article analyzes the strategic interests of Uzbekistan and the constantly changing regional context; there is the opinion that the Republic of Uzbekistan holds prime responsibility for the regional situation. This issue calls for a detailed analysis—here I shall take a look at some of the elements of what is known as the state’s Grand Strategy.